2019
DOI: 10.1186/s12245-019-0254-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploring emergency department visits: factors influencing individuals’ decisions, knowledge of triage systems and waiting times, and experiences during visits to a tertiary hospital in Saudi Arabia

Abstract: BackgroundIn recent years, there has been an increased utilization of emergency departments (EDs) in many countries. Additionally, it is reported that there are major delays in delivering care to ED patients. Longer waiting times are associated with poor patient satisfaction, whereas an understanding of the triage process increases satisfaction. This study aimed to assess ED visitor’s awareness of the triage procedure and their preferences regarding delayed communication.MethodsCross-sectional study of King Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
29
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 22 publications
6
29
3
Order By: Relevance
“…Emergency department overcrowding is becoming a challenge for the healthcare management system globally 22 and locally. 1 In Saudi Arabia, studies about ED visits mainly focus on a specific study population, ie drug-related problems, 23 triage system issues, 24 non-urgent visits, 25 duration of revisit, 26 or a specific group of patients, ie post bariatric surgery 27 and sickle-cell disease. 28 To our knowledge, the current study is among the few targeting all the adult patients frequenting the emergency department in tertiary care in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergency department overcrowding is becoming a challenge for the healthcare management system globally 22 and locally. 1 In Saudi Arabia, studies about ED visits mainly focus on a specific study population, ie drug-related problems, 23 triage system issues, 24 non-urgent visits, 25 duration of revisit, 26 or a specific group of patients, ie post bariatric surgery 27 and sickle-cell disease. 28 To our knowledge, the current study is among the few targeting all the adult patients frequenting the emergency department in tertiary care in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The current study shows that female patients had more visits (53%), which supports local studies, (55%) females reported by Al-Otmy etal; (57%) by Zakaria etal, and international literature Hooker etal Yet, a study has yielded equal numbers of ED visits by males and females. 24 In general, studies have reported different distribution of frequent visitation across gender; males dominance was reported in Singapore, 9 in females 31 or unrelated to gender. 35 It has been reported in the literature that when visiting frequency increases, the percentage of males increases.…”
mentioning
confidence: 99%
“…However, the preferred way of information dispensation at the ED was only based on non-European studies with varying results. The preferred way of information delivery was by lea ets (32-60%), video (25-50%) or speaking with an expert (24%) (11,12,16). The option for modern techniques such as apps on personal devices or tablets provided by the hospital were not studied before.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is little evidence regarding the preferred way of information dispensation at the ED and only based on non-European studies. These studies showed that patients preferred information dispensation by video, lea ets or information screen in the waiting room (11,12,16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation